Bimatoprost versus clobetasol propionate in scalp alopecia areata: A prospective non-randomized open-label clinical trial - Mohan Bhusal; Sabina Bhattarai; Binita Thapa; Prashanna R Shrestha; G C Sagar (Wolters Kluwer Medknow Publications, 2023)
Background: Alopecia areata (AA) is one of the most common forms of alopecia presenting to the dermatology out patient department (OPD) worldwide as well as in Nepal. It is mostly diagnosed clinically. Treatment depends on the extent, location, and severity of the condition. Various treatment options available are topical, intralesional, and oral medications. Bimatoprost is a relatively newer treatment modality in AA. Aim and Objective: To compare the efficacy and safety of topical bimatoprost 0.01% solution versus clobetasol propionate 0.05% cream in scalp AA. Materials and Methods: A total of 50 patients attending the dermatology OPD of a tertiary hospital between March 2018 and February 2019 were included in this prospective non-randomized open-label clinical trial. Patients were divided into two groups i.e., Group A- topical bimatoprost solution 0.01% and Group B- topical clobetasol propionate cream 0.05%, and followed up at weeks 4, 8, and 12. The improvement was analyzed subjectively by hair regrowth and objectively by Severity of Alopecia Tool (SALT) score. Side effects, nature of terminal hair and onset of initial response were also recorded. Results: Out of 50 patients, 27 were males and 23 were females with a mean age of 28.5 ± 9.34 years and mean duration of disease of 18.67 ± 46.1 weeks. Hair regrowth rate and reduction in SALT score from baseline were seen more in clobetasol group compared to bimatoprost (p = 0.282 and P = 0.246, respectively). Side effects were seen more in the clobetasol group compared to bimatoprost group (p = 0.002). Onset of cosmetically acceptable hair regrowth was seen earlier in the bimatoprost group (p = 0.017) and also the nature of regrown hairs was more pigmented in bimatoprost group (p = 0.024). Conclusions: There is no significant difference in hair regrowth between clobetasol and bimatoprost in the treatment of AA on scalp at the end of 12 weeks, although bimatoprost has an advantage of lesser side effects, more rapid response and growth of more pigmented hairs.